2020
DOI: 10.1017/jgc.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the ethical dilemmas of school counsellors: opinions and solution recommendations

Abstract: Ethical dilemmas are concerning for school counsellors in Turkey. This article presents findings of a qualitative study exploring the views and suggestions of 16 school counsellors in Rize, Turkey. Content analysis was performed on the data obtained from interviews with the participants. The results of the study showed that the school counsellors had the most knowledge about the competency principle of school counselling codes of ethics. The study also showed that regarding legal aspects of school counselling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…İkiz and Camadan (2021) revealed that teachers mostly experience ethical dilemmas regarding professional and scientific responsibility. Camadan et al (2020) found that teachers frequently encounter ethical dilemmas related to job-related ethical and legal rules, encompassing areas such as privacy, competence, and willingness. In the study conducted by Özivgen and Karaçam (2020), no significant differences were observed between teachers' ethical dilemmas and various subdimensions (behavioral, structural, political, and systemic) in relation to age, length of service, gender, and type of institution.…”
Section: Introductionmentioning
confidence: 99%
“…İkiz and Camadan (2021) revealed that teachers mostly experience ethical dilemmas regarding professional and scientific responsibility. Camadan et al (2020) found that teachers frequently encounter ethical dilemmas related to job-related ethical and legal rules, encompassing areas such as privacy, competence, and willingness. In the study conducted by Özivgen and Karaçam (2020), no significant differences were observed between teachers' ethical dilemmas and various subdimensions (behavioral, structural, political, and systemic) in relation to age, length of service, gender, and type of institution.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature in Turkey defines sources of dilemmas for school counsellors as confidentiality and competencies (İkiz et al, 2017), conflicts with school leaders, dual relationships, boundary issues (Siviş-Çetinkaya, 2015a), and title confusions (Arslan et al, 2019). Camadan et al (2020) also revealed the top three kinds of information for school counsellors in the context of counselling ethics to be competence, continuing professional development, and sensitivity. To our knowledge, only one study has examined the ethical judgments of Turkish counsellors, and that research was not specific to school counsellors (Siviş-Çetinkaya, 2015c).…”
mentioning
confidence: 99%